Learning English through Hearthstone: Research on Students’ Perceptions and Strategies - Kriswanda Krishnapatria (ELT in Focus, 2022)
This research aims to describe and explain the students’ perception of English learning through the card game Hearthstone for students in the English Studies program. In COVID-19, there has been an increase in playing time with online games, including Hearthstone. Spending too much time on gaming activities may be problematic, but it can also help students learn English sensibly. Thus, this research focuses on discovering students’ perceptions of learning English using a collectible card game (CCG) online game. The researcher used an online survey due to physical distancing regulations in this qualitative research. Using purposive sampling, the writer chose three students from the English Studies program who played Hearthstone routinely during the pandemic as a source of entertainment and learning activity. The interview result showed that all respondents generally had excellent and positive perceptions about English learning through Hearthstone. They were more interested and more motivated in learning English through Hearthstone because it was fun, enjoyable, and challenging. It also showed that all respondents had their strategies in the learning process, consisting of three steps: planning, monitoring, and evaluation. Despite its attached negative stigma, an online game like Hearthstone turned out to be beneficial in helping students learn English amid the COVID-19 outbreak.